Nietzsche e a crítica ao historicismo: uma análise a partir da relação entre história e vida na segunda consideração intempestiva. - Lima, Márcio José Silva (2012)
The present work has for purpose analyze through a interpretative reading, the critical of the Nietzsche to the historicism starting from the relationship between history and life. The historicism is understood in this dissertation as the exaggerating use of the historical knowledge, the faith in a philosophy of the history as it presented the Hegelianism and the objectivity of the history while modern science. According to Nietzsche, the way the story was conceived in the nineteenth century, it turned the life sick and degenerate. The excess of historical culture removed the power of man's own creation and it restricted the mere reproduction of the past. The past was seen as a model to be copied, therefore, influenced by the philosophy of history that pointed to a becoming by an entity determined by metaphysics and scientism which conceived of history as a science that accurately describes the past, man has become incapable create and passed only to live the history of others, the history of those that had died. Humanity has become old, obsolete, without vitality. In this context, on his Second Untimely, the German philosopher appears for that that would be a profitable use of the history to service of the life. Reflecting her usefulness and her disadvantage, the thinker addresses the directions of the history for another sense. A new way to conceive the history as creative activity in extreme consonance with the life.